IL-15Rα-Independent IL-15 Signaling in Non-NK Cell-Derived IFNγ Driven Control of Listeria monocytogenes - Nandi, Madhuparna; Moyo, Mitterrand Muamba; Orkhis, Sakina; Mobulakani, Jeanne Masunga Faida; Limoges, Marc-André; Rexhepi, Fjolla; Mayhue, Marian; Cayarga, Anny Armas; Marrero, Gisela Cofino; Ilangumaran, Subburaj; Menendez, Alfredo; Ramanathan, Sheela (Frontiers in Immunology, 2021)
Interleukin-15, produced by hematopoietic and parenchymal cells, maintains immune cell homeostasis and facilitates activation of lymphoid and myeloid cell subsets. IL-15 interacts with the ligand-binding receptor chain IL-15Rα during biosynthesis, and the IL-15:IL-15Rα complex is trans-presented to responder cells that express the IL-2/15Rβγc complex to initiate signaling. IL-15-deficient and IL-15Rα-deficient mice display similar alterations in immune cell subsets. Thus, the trimeric IL-15Rαβγc complex is considered the functional IL-15 receptor. However, studies on the pathogenic role of IL-15 in inflammatory and autoimmune diseases indicate that IL-15 can signal independently of IL-15Rα via the IL-15Rβγc dimer. Here, we compared the ability of mice lacking IL-15 (no signaling) or IL-15Rα (partial/distinct signaling) to control Listeria monocytogenes infection. We show that IL-15-deficient mice succumb to infection whereas IL-15Rα-deficient mice clear the pathogen as efficiently as wildtype mice. IL-15-deficient macrophages did not show any defect in bacterial uptake or iNOS expression in vitro. In vivo, IL-15 deficiency impaired the accumulation of inflammatory monocytes in infected spleens without affecting chemokine and pro-inflammatory cytokine production. The inability of IL-15-deficient mice to clear L. monocytogenes results from impaired early IFNγ production, which was not affected in IL-15Rα-deficient mice. Administration of IFNγ partially enabled IL-15-deficient mice to control the infection. Bone marrow chimeras revealed that IL-15 needed for early bacterial control can originate from both hematopoietic and non-hematopoietic cells. Overall, our findings indicate that IL-15-dependent IL-15Rα-independent signaling via the IL-15Rβγc dimeric complex is necessary and sufficient for the induction of IFNγ from sources other than NK/NKT cells to control bacterial pathogens.